2015
DOI: 10.4137/ebo.s31326
|View full text |Cite
|
Sign up to set email alerts
|

Genomics and Evolution in Traditional Medicinal Plants: Road to a Healthier Life

Abstract: Medicinal plants have long been utilized in traditional medicine and ethnomedicine worldwide. This review presents a glimpse of the current status of and future trends in medicinal plant genomics, evolution, and phylogeny. These dynamic fields are at the intersection of phytochemistry and plant biology and are concerned with the evolution mechanisms and systematics of medicinal plant genomes, origin and evolution of the plant genotype and metabolic phenotype, interaction between medicinal plant genomes and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 113 publications
(191 reference statements)
0
24
0
1
Order By: Relevance
“…Here we have combined both the phylogenetic and ethnobotanical approaches by choosing a geographically-widespread plant family, reconstructing a molecular phylogeny for the family, mapping ethnobotanical data onto the resulting phylogeny, and evaluating correlations between the evolutionary relatedness of the species and their ethnobotanical uses by different cultural groups who live in different geographic regions. Studies such as this that utilize phylogenetic patterns of medicinal properties within plant lineages are few [10,[21][22][23][24][25][26][27][28][29]. Saslis-Lagoudakis et al [10] concluded that phylogenetic cross-cultural comparisons can focus screening efforts on the closest relatives of medicinal plants already in use as traditional medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Here we have combined both the phylogenetic and ethnobotanical approaches by choosing a geographically-widespread plant family, reconstructing a molecular phylogeny for the family, mapping ethnobotanical data onto the resulting phylogeny, and evaluating correlations between the evolutionary relatedness of the species and their ethnobotanical uses by different cultural groups who live in different geographic regions. Studies such as this that utilize phylogenetic patterns of medicinal properties within plant lineages are few [10,[21][22][23][24][25][26][27][28][29]. Saslis-Lagoudakis et al [10] concluded that phylogenetic cross-cultural comparisons can focus screening efforts on the closest relatives of medicinal plants already in use as traditional medicines.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that chemometric analyses such as reversed-phase high-performance liquid chromatography and biochemical markers can be used for analyzing and classifying intra-specific genetic relationship of plant populations [20,21]. Nowadays, scientists are encouraged to bioinformatics technics and the omics-based approaches in traditional medicine and ethnomedicine studies [22][23][24][25] which can be of help to manage the herbal research as large-scale datarich studies.…”
Section: Discussionmentioning
confidence: 99%
“…Whole‐genome sequences of medicinal plants are a vital resource for understanding total biosynthetic potential. It also promote the development of natural medicines and the selection of cultivars with good agricultural traits and high levels of desired metabolites of medicinal and pharmaceutical importance (Hao and Xiao, ; Unamba et al ., ). Dependence on medicinal plants for the extraction of important bioactive metabolites has proved to be an unsustainable approach (Chang and Keasling, ; Facchini et al ., ); therefore, knowledge of biosynthetic pathway elements provides an opportunity to develope alternate sources for these compunds.…”
Section: Omics Toolsets and Analysis To Discover Unknownsmentioning
confidence: 99%
“…So far, whole‐genome sequences of 183 land plants have been released in the NCBI Genome database, 58 being completed and submitted in 2016 alone (a total of 68 genome sequences were released in 2016) (Table ) with 23 plant species being used primarily for medicinal purposes or described in different traditional medicinal practices. Genomic sequences provide essential information on plant origin, evolution, inheritable traits, developmental and physiological schematics, epigenomic regulation and metabolic potential, which serve as the basis for deciphering genome diversity and chemo‐diversity at the molecular level (Dhanapal and Govindaraj, ; Hao and Xiao, ; Unamba et al ., ). Genomic sequences assist in the development of accessible and robust functional genomic resources, such as full‐length complementary DNA clone sets, tagged mutant lines and a rapid and facile transformation method.…”
Section: Omics Toolsets and Analysis To Discover Unknownsmentioning
confidence: 99%
See 1 more Smart Citation